2020
DOI: 10.1002/mma.6919
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation for the mixed convective flow of non‐Newtonian fluid with activation energy and entropy generation

Abstract: Here, mathematical modeling is performed for the nonlinear mixed convection in dissipative convective flow of micropolar fluid towards a stretched surface. Mixed convection occurs when both forced and natural convection mechanisms act together. Mixed convection problems are categorized by Grashof number. This is also addressed as situations where both buoyant and pressure forces interact. Slip condition is considered at the boundary for the velocity. Magnetohydrodynamics (MHD) fluid is considered. Novel featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The constant disk heat temperature can be achieved by exposing the surface to a material that is undergoing a phase change. The local Nusselt number along the flow direction at different radial positions was computed for a fixed disk temperature of 373 K and an ambient temperature of 300 K. 29 The water at 300 K was taken as the working fluid. The local Nusselt number is defined as…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The constant disk heat temperature can be achieved by exposing the surface to a material that is undergoing a phase change. The local Nusselt number along the flow direction at different radial positions was computed for a fixed disk temperature of 373 K and an ambient temperature of 300 K. 29 The water at 300 K was taken as the working fluid. The local Nusselt number is defined as…”
Section: Resultsmentioning
confidence: 99%
“…A magnetohydrodynamic (MHD) micropolar fluid approaching a stretched surface is investigated numerically by Khan and Alzahrani. 29 The effects of forced and natural convections are included in the mathematical model. The slip boundary condition and convective condition are used on the solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofluids have unique features that make them suitable for use in a variety of heat transfer systems, including microelectronics, solar collectors, cancer therapy, fuel cells, household refrigerators, pharmaceutical operations, engine cooling thermal management, hybrid‐powered engines, boiler flue gas temperature reduction and heat exchanger, and many more; see Salawu et al, 22 Fatunmbi and Salawu, 23 and Khan et al 24 Hayat et al 25 investigated the motion of electrically conducting second‐grade nanofluid induced by stretching sheet using the Buongiorno model characterized by Brownian motion and thermophoresis effects. Ijaz Khan and Alzahrani 26 performed a numerical simulation for the micropolar nonlinear mixed convective transport via the Buongiorno model with the impact of chemical reaction. It is worth deducing from the reports of Kuznetsov and Avramenko, 15 Beg et al, 16 and Mahdy 17 that the suspension of bioconvective gyrotactic microorganism phenomena in a nanofluid is a promising platform for increasing heat convection and conduction of nanoparticles in the base liquid.…”
Section: Introductionmentioning
confidence: 99%
“…For a mixed convective mechanism, moving surfaces acquire the opposite effectiveness under a great mixed convection parameter and it also impacts the rate of thermal variation prominently. [2][3][4] Kumari and Nath 5 explained the influence of the suction/injection and heating/cooling on combined convective flow over an orthogonal slender cylinder. The results showed that positive buoyancy force helps the flow and the curvature parameter enhances the skin friction and heat transport.…”
Section: Introductionmentioning
confidence: 99%